Surface Electromyography in Physiotherapist Educational Program in France: Enhancing Learning sEMG in Stretching Practice - Portero, Pierre; Dogadov, Anton A.; Servière, Christine; Quaine, Franck (Frontiers in Neurology, 2020)
Surface electromyography (sEMG) is a non-invasive method, which may be used in France by health practitioners without medical degree, such as physiotherapists, who are taught in Institutes of physiotherapy. However, very few hours are devoted to sEMG teaching in physiotherapist educational programs, especially in a form of practical work. In order to motivate using sEMG in physiotherapy to the students, we propose an example of sEMG practical work, applied to muscle stretching. Passive stretching exercises are often used by physiotherapists to maintain or improve range of motion. During a passive stretching session, subjects are given specific instructions to relax and not to activate their muscles during the procedure. In the proposed practical work, the sEMG is used to study the plantar flexor activation level during passive stretching. Therefore, this work may provide students with deeper understanding of physiology and biomechanics, trigger an interest in sEMG as a tool, and give knowledge about good sEMG practice, according to SENIAM and other recommendations. The integration of Institutes of physiotherapy in the University system may provide an opportunity to revisit the physiotherapist educational program and to provide students with more practical courses on sEMG application.